Synthesis and SAR of novel GPR39 agonists and positive allosteric modulators. (1st April 2022) - Burley, Russell; Hewer, Richard C.; Teall, Martin; Dickson, Louise; Ossola, Bernardino; Russell, Sam; Bender, Clare; Cheung, Toni; Powell, Justin A.C.; Xu, Xiao; Brice, Nicola L.; Otter, Lucy; et al.
Graphical abstract: Abstract: We report a significant decrease in transcription of the G protein-coupled receptor GPR39 in striatal neurons of Parkinson's disease patients compared to healthy controls, suggesting that a positive modulator of GPR39 may beneficially impact neuroprotection. To test this notion, we developed various structurally diverse tool molecules. While we elaborated on previously reported starting points, we also performed an in silico screen which led to completely novel pharmacophores. In vitro studies indicated that GPR39 agonism does not have a profound effect on neuroprotection.